Effectiveness of "Butterfly" rotary sprinkler on dry land. Issue 1 (April 2020) - Faridah, S N; Samsuar,; Suhardi,; Munir, A; Achmad, M
Abstract: Sprinkler irrigation is an irrigation application technology, which has high efficiency in the use of water; it is very appropriate to be applied in a relatively dry area. In its application, the high effectiveness of sprinkler irrigation systems can only be achieved if properly designed irrigation system and is operated properly. This research was conducted by designing irrigation networks. The irrigation application uses a butterfly sprinkler with a nozzle diameter size of 2 mm and 4 mm and pressure treatment to get the effectiveness of the irrigation system performance. Butterfly sprinkler with a nozzle diameter of 2 mm, effectively used at a pressure of 10-20 Psi, with a spray radius of 3.90 - 5.70 meters, watering discharge 6.49 - 8.10 liters/minute and water uniformity distribution 88.3 - 90.8 %. As for the 4 mm nozzle diameter, it is effective used at a pressure of 15-30 Psi, with a spray radius of 4.90 - 6.00 meters, a watering discharge of 9.98 - 14.83 liters/minute and a water uniformity distribution of 90.4 – 91.7 %.